(untitled) (Iraqi Journal of Civil Engineering, 2024)
The buckling analysis of Euler-Bernoulli beam resting on two-parameter elastic foundation (EBBo2PEF) has important applications in the analysis and design of foundation structures, buried gas pipeline systems and other soil-structure interaction systems under compressive loads. This study investigates the buckling analysis of EBBo2PEFs. The governing differential equation of elastic stability (GDiES) is derived in this work using first principles equilibrium method. In general, the GDiES is an inhomogeneous equation with variable parameters for non-prismatic beams under distributed transverse loadings. However, when transverse loads are absent and the beam is prismatic the GDiES becomes a fourth order ordinary differential constant parameter homogeneous equation. General solution to GDiES is obtained in this work using the classical trial exponential function method of solving equations. Two cases of end supports were considered: simply supported ends and clamped ends. Boundary conditions (BCs) were used to obtain the characteristic buckling equations whose eigenvalues were used to determine the critical buckling loads for two cases of BCs considered. It was found that the method gave exact solutions for each of the BCs. The critical elastic buckling load coefficients for dimensionless beam-foundation parameter and ranging from for simply supported EBBo2PEFs were identical with previous results that used Stodola-Vianello iteration methods and finite element method. Similarly, the critical buckling load coefficients for and are identical with previous results that used Ritz variational method.